Meningkatkan Aktivitas Dan Hasil Belajar Siswa Dengan Model Pbl, Mind Mapping Dan Talking Stick Muatan IPS Pada Siswa Kelas IV Di SDN Ambakiang Kabupaten Balangan - Saidatin Halifah; Amberansyah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in the study of low activity and learning outcomes in the fourth grade students of SDN Ambakijang Regency Balangan IPS load. The reason (1) students pay less attention during learning, (2) students are afraid of expressing opinions, (3) less attractive learning, (4) students become bored. One effort to resolve the problem with the PBL model, Mind Mapping and Talking. This study aims to determine whether the PBL model, Mind Mapping and Talking Stick can increase the activities and learning outcomes of students of IPS loads in class IV students at SDN Ambakiang Balangan Regency. This research is a PTK consisting of 4 meetings. The subject in this study was all fourth grade students of SDN Ambrikiang. This PTK uses data collection methods, namely written tests, observation sheets, documentation. Data analysis uses qualitative and quantitative analysis techniques. Based on the results of this study show that with the PBL model, Mind Mapping and Talking Sticks can increase class IV's activities and learning outcomes at SDN Ambakiang Balangan Regency. This was seen at the 4th meeting indicating that teacher activities obtained a 100% score of a very good category. Student activity obtained a score of 90% of the very active categories, and learning outcomes obtained a 100% score. Based on the findings it can be concluded that PBL, Mind Mapping and Talking Stick can increase student learning and learning outcomes.